2007
DOI: 10.1159/000103263
|View full text |Cite
|
Sign up to set email alerts
|

Placement of Intraventricular Catheters Using Flexible Electromagnetic Navigation and a Dynamic Reference Frame: A New Technique

Abstract: Background: Catheterization of narrow ventricles may prove difficult resulting in misplacement or inefficient trials with potential damage to brain tissue. Material and Methods: The application of a new module for navigated ventricular catheterization using flexible electromagnetic navigation and a dynamic reference frame is presented. Results: Navigated catheter placement was successful and accurate in a pilot study. Electromagnetic interferences had to be taken into consideration. Conclusion: Flexible electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
(18 reference statements)
0
16
0
1
Order By: Relevance
“…It obviates the need for sharp head fixation offering a good alternative to optoelectric techniques, there are no line-of-sight problems, the position of the patient can be changed during surgery, and it allows the use of flexible instruments [24,31,33]. While it was shown to be beneficial especially in the placement of ventricular catheters for different indications [23,24,31,33,43,44], its advantages have been demonstrated also for many other neurosurgical procedures [22,25,26,27,34,45,46,47]. Studies on the accuracy of EM navigation have shown that it is comparable to optoelectric navigation ranging between 0.71-3.51 mm [48] and 0.7-4.4 mm [49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It obviates the need for sharp head fixation offering a good alternative to optoelectric techniques, there are no line-of-sight problems, the position of the patient can be changed during surgery, and it allows the use of flexible instruments [24,31,33]. While it was shown to be beneficial especially in the placement of ventricular catheters for different indications [23,24,31,33,43,44], its advantages have been demonstrated also for many other neurosurgical procedures [22,25,26,27,34,45,46,47]. Studies on the accuracy of EM navigation have shown that it is comparable to optoelectric navigation ranging between 0.71-3.51 mm [48] and 0.7-4.4 mm [49].…”
Section: Discussionmentioning
confidence: 99%
“…Movements of the head during surgery do not lead to navigation inaccuracy. Therefore it is especially advantageous in shunt surgery [24,31,33]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although high accuracies are required, which usually points to optical tracking as method of choice, a few researchers have navigated neurosurgical interventions using EM tracking [174,134]. In some cases, namely placement of depth electrodes for epilepsy treatment [200] or catheter placement in the cerebral ventricular system [155], line-of-sight is blocked and so EM tracking is the only option to track the instrument. EM tracking also was used during open liver surgery in combination with an optical tracking system [10].…”
Section: A Range Of Applicationmentioning
confidence: 99%
“…Electromagnetic tracking systems offer many advantages over optical tracking systems, especially in the field of pediatric neurosurgery, such as for insertion of ventriculoperitoneal shunts, electromagnetic navigation-assisted rigid endoscopic procedures, and intraventricular catheter placement. 7,15,19,23) Electromagnetic navigation systems were created in 1991, with a computer-assisted neurosurgical navigational system using a magnetic source and sensor. 12) Since then, many in vivo and in vitro uses have been reported, and registration error as calculated by the various systems currently varies between 0.7 mm and 4.4 mm, showing no difference in accuracy compared with current optical navigation systems.…”
Section: Discussionmentioning
confidence: 99%